Needs Analysis on English for Computer in SMK Negeri 1 Pematangsiantar - Rajagukguk, Mutiara; Hutauruk, Bertaria Sohnata; Sinaga, Yanti Kristina (Innovative: Journal Of Social Science Research, 2024)
English is one of the general subjects that must be taken by every student in Vocational High School. English learning for students must be based on a learning needs analysis in order to obtain the benefits of learning English according to their needs. The purpose of this study was to analyze the needs, deficiencies, and desires of students in the English for Computer course and English teaching for SMK students majoring in Computer in class 11 of SMK Negeri 1 Pematangsiantar. The method used in this study is qualitative. This study uses a needs analysis with a survey design. The instrument used in this study was a semi-closed questionnaire. a series of questionnaires were distributed to 34 respondents from the computer department. From the needs analysis, it was found that students need English to improve their speaking, listening, reading, and writing skills. The results of the study also showed that the purpose of students learning English is to compete in the world of work. The skills that are prioritized are speaking and reading skills with a focus on vocabulary related to computer science. In speaking skills activities, most students prefer to have a dialogue and then practice with friends.